Integrated Steering System Design for Bus Driver Drowsy Behavior Change - Tan, CheeFai; Ranjit Singh, Sarban Singh; V.K., Kher; B.T., Tan (Trans Tech Publications, Switzerland, 2013)
The paper presents an integrated steering system design for bus drivers’ drowsy driving behaviour change. Busses involved in accidents due to drowsy driving is increasing nowadays and those accidents involved a lot of people due to the number of passengers it carries. In order to decrease the rate of accidents for bus driver due to drowsy driving, an integrated steering system that can change their driving behaviour is developed. The developed integrated steering system is then being validated through surveys conducted on drivers with valid driving licence. The survey results have shown that the integrated steering system is a feasible system to the drivers.